MENGEMBANGKAN KESADARAN DIRI PADA SISWA UNTUK MENCEGAH TINDAK PERUNDUNGAN DI SEKOLAH DASAR - Puspitasari, Puspitasari (Dharmas Education Journal (DE_Journal), 2023)
Bullying is still a problem that often occurs in elementary schools. To prevent acts of bullying, holistic efforts are needed, one of which is to develop self-awareness in students. This article aims to discuss the importance of developing self-awareness in students to prevent acts of bullying in elementary schools. This study used a literature study which was conducted by searching for journals and articles related to developing self-awareness in students and preventing acts of bullying in elementary schools. The data collected from the literature study is used to provide an overview of the concepts and theories related to the discussion. Based on the results of the study that self-awareness can increase students' empathy for other people, helping students to better understand the feelings and needs of other people. In this case, students will be more sensitive to their surroundings and become more empathetic towards their classmates. Thus, students will be better able to avoid bullying behavior and be able to help friends who are experiencing problems